Sikap Toleransi Melalui Pembelajaran Multikultural Pada Siswa Sekolah Dasar - Yumnafiska Aulia Dewi; Mardiana Mardiana (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2023)
Multicultural education has been a part of the Indonesian education system since Ki Hajar Dewantara. This system can help eradicate discriminatory attitudes towards race, religion, ethnicity, culture, and language differences if properly implemented. However, intolerance remains a significant problem in various parts of Indonesia. Implementing multicultural education is hoped to instill a deep understanding of tolerance among students. This research employs a literature review methodology, which involves collecting and analyzing data from various library sources such as books, journals, and websites. The type of research used is qualitative research, which offers a more in-depth analysis of a narrower scope. The study concludes that tolerance is an attitude of appreciation and respect for others, and multicultural education emphasizes character education, particularly in promoting tolerance through multiculturalism-based learning. This approach can give students from diverse backgrounds a unique understanding and appreciation of one another.Keywords: Tolerance; intolerance; multicultural education; education system.